Social Lesions In Al-Mamluki Era: (Al-Hashisha Poetry as A model) - ABDULQADER IMRAN, MAYYADAH (Al-Adab Journal, 2021)
The research dealt with a widespread phenomenon in the later eras, especially in Al – Mamluki era. Which is Marijuana (Al –Hashisha) as a result of what society had faced of oppressive circumstances. Which resulted in a social scourge that people misused them, particularly among popular peoples (The poor). Where they had them more to make them forget their miserable reality of life. So, poets of that era wanted to express their anger and revulsion from this scourge through their poems. So, they adopted two directions: The first group supported it, because it makes the drinker feels with pleasure in the soul and removes it from his painful reality. The second collection had rejected it because it brings diseases, fatigue and may lead his life to death.